DAMPAK DARI KETERLIBATAN MENGGUNAKAN LISTRIK PINTAR DARI DAYA BELI MASYARAKAT PADA EKONOMI RUMAH TANGGA - Johni Paul Karolus Pasaribu (Management and Sustainable Development Journal, 2022)
The purpose of this research is to measure people's purchasing power in the use of electrical energy with household involvement and economy. The research method using clusters and using a questionnaire as a medium to collect information, the sample used is 100 households. The results of the study show that only purchasing power in the price is significant in the household economy, prices and income are significant in the involvement, significant involvement in the household economy. Indirectly only prices and income in purchasing power are significant to the household economy through the involvement of management and use of electrical energy.